PENGARUH TINGKAT KEDISIPLINAN DAN TANGGUNG JAWAB KARYAWAN TERHADAP PRODUKTIVITAS KERJA DI PT KAWAI PIANO INDONESIA - N.Neni Triana; Ahmad Hilmi Insani (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
There are many factors that affect productivity including the number of hours worked, quality of work, morale, work discipline, efficiency and effectiveness of work. The purpose of the study was to determine the effect of work discipline and responsibility on work productivity at PT. Kawai Piano Indonesia. The population of this study were all employees of PT. Kawai Piano Indonesia, with an error rate of 5% with a sample of 100 employees. The quantitative research method uses linear regression with SPSS 25. The results of the study at a significance level of 5% indicate that: (1) There is a simultaneous influence of discipline in company discipline and discipline in work responsibilities on work productivity at PT. Kawai Piano Indonesia. This is evidenced in the ANOVA table, the value of f-count > f-table (60.688 > 3.09) is obtained. (2) There is the ability of the independent variable, namely discipline in company regulations and discipline in responsibility at work in explaining variations in changes in the productivity dependent variable, which is 54.7%, while the remaining 45.3% is explained by other factors.